An Improved Convolutional Neural Network for Plant Disease Detection Using Unmanned Aerial Vehicle Images - Dashuang Liang, Wenping Liu, Lei Zhao, Shixiang Zong and Youqing Luo (Nature Environment and Pollution Technology, 2022)
Accurate and fast locating of diseased plants is critical for the sustainability of forest management. Recent developments in computer vision made by deep learning provide a new way for diseased plant detection from images captured by unmanned aerial vehicles (UAV). In this paper, we developed an anchor-free detector, an enhanced CenterNet named as Enhanced CenterNet (ECenterNet) model, which significantly improved the overall accuracy over the original CenterNet model without any increase in the running speed or number of parameters. Compared with the original model, in the newly proposed model improvements had been made in the training stage to increase the accuracy of the detector, while procedures in the test stage remained unchanged. Under the hold-out dataset, the proposed model is trained on 5,281 tiles and tested on 3,842 images, the results showed that the overall detection accuracy of ECenterNet reached 54.7% by COCO Challenge metrics (mean average precision (mAP) @[0.5, 0.95]), while mAP accuracy of the original CenterNet was 49.8%. This research indicates that the proposed deep learning detection model provides a better solution for detecting diseased plants from UAV images with high accuracy and real-time speed.